2010
DOI: 10.1111/j.1755-3768.2010.02026.x
|View full text |Cite
|
Sign up to set email alerts
|

Micropulse diode laser trabeculoplasty – 180‐degree treatment

Abstract: Abstract.Purpose:  To evaluate the outcome of 180° micropulse diode laser trabeculoplasty (MDLT) in patients with open‐angle glaucoma.Methods:  A retrospective review of 40 eyes of 29 MDLT‐treated patients with a minimum follow‐up time of 6 months. Successful outcome was defined as follows: (i) a ≥20% or (ii) a ≥3‐mmHg decrease of intraocular pressure (IOP), no further need for laser‐ or incisional surgery and the number of glaucoma medication was the same or less than preoperative. These definitions will from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…In the present study, eyes with a lower number of medications did not have a better success rate than eyes with ≥ 3 medications. This observation was in agreement with our previous study on 180-degree MDLT treatment [16]. …”
Section: Discussionsupporting
confidence: 94%
“…In the present study, eyes with a lower number of medications did not have a better success rate than eyes with ≥ 3 medications. This observation was in agreement with our previous study on 180-degree MDLT treatment [16]. …”
Section: Discussionsupporting
confidence: 94%
“…24 In our study, 73% of eyes that received 360° treatment achieved success with MLT. Our findings were consistent with Fea et al who reported using the 810 nm MLT that 75% of treated patients had an IOP reduction, with 60% of patients having >20% IOP reductions.…”
Section: Discussionmentioning
confidence: 48%
“…The success rates for MLT were higher than some previously reported studies involved in achieving the goal of ≥3 mmHg IOP or ≥20.0% IOP reduction from baseline values, although one author utilized the 810 nm diode laser12 and the other only targeted the inferior meshwork 15. Our findings were also less efficacious than some reports, but had a smaller sample size11 and included shorter intervals of follow-up 16…”
Section: Discussionmentioning
confidence: 59%
“…In 2012, Rantala and Välimäki12 also studied 180° MLT treatment with the 810 nm diode laser, concluding that only 2.5% of patients experienced a ≥20.0% IOP decrease from baseline and 7.5% of patients had a ≥3 mmHg IOP decrease without further intervention. Conversely, Babalola13 utilized the 810 nm diode laser applied to the inferior 180° for MLT in a Nigerian population with a sustained IOP lowering effect from weeks to months with an average IOP decrease of 17.2%.…”
Section: Discussionmentioning
confidence: 99%